PF-35 Spider Silk (Nephilia sp.) as Suture Material on Blood Vessel Surgery - S W Cheng; B J Widyananta; B P Priosoeryanto (Hemera Zoa, 2018)
Surgical suture is a medical device used to hold body tissues together after an injury or surgery. Application generally involves using a needle with an attached length of thread. Surgical sutures are normally classified into two types, absorbable and non-absorbable. They can also be classified based on their construction, either mono-filament or multi-filament and also whether they are made from natural or synthetic materials. Sutures can also be classified according to their usage e.g. cardiovascular sutures, ophthalmic sutures, general sutures, orthopaedic sutures etc. Common problems associated with the choice of suture material include increased risk of infection, foreign body reactions, and inappropriate mechanical responses, particularly decreases in mechanical properties over time. Improved suture materials are therefore needed. As a high- performance material with excellent tensile strength, spider silk fibres are an extremely promising candidate for use in surgical sutures. However, the biochemical behaviour of individual silk fibres braided together has not been thoroughly investigated. In the present study, we characterise the inflammatory response produced from silk sutures and absorbance time.